Rancangan Konsep Pencegahan Dan Peningkatan Kualitas Permukiman Kumuh Di Kelurahan Bonerato Kabupaten Tojo Una-Una - Fratika Julia; Fitriah Fajar Maghfirah; Rachmat Saleh; Khaerunnisa Laguni (Jurusan Teknik Arsitektur, Fakultas Teknik Universitas Tadulako Kampus Bumi Tadulako Tondo Jl. Sukarno-Hatta Km.9, Palu 94118 e-mail :Jurusan Arsitektur, Fakultas Teknik Universitas Tadulako Kampus Bumi Tadulako Tondo Jl. Sukarno-Hatta Km.9, Palu 941, 2024)
Slums are one of the urban problems that impact environmental quality, public health, and regional sustainability. Bonerato Village in Tojo Una-Una Regency faces various settlement problems such as limited basic infrastructure, inadequate sanitation, poor drainage, and low quality of community housing. This study aims to formulate a concept for preventing and improving the quality of slum settlements through an architectural and regional planning approach. The research method uses a qualitative descriptive approach with field observations, interviews, and analysis of the physical conditions of the environment. The results show that the concept of handling slum settlements can be implemented through improving the quality of basic infrastructure, environmental spatial planning, providing green open spaces, community-based sanitation management, and strengthening community participation in area management. This concept is expected to create a healthy, safe, and sustainable residential environment.